Lysophosphatidic acid induces the crosstalk between the endovascular human trophoblast and endothelial cells in vitro. Issue 5 (26th October 2018) - Beltrame, Jimena S.; Scotti, Leopoldina; Sordelli, Micaela S.; Cañumil, Vanesa A.; Franchi, Ana M.; Parborell, Fernanda; Ribeiro, María L.
Abstract: Spiral artery remodeling at the maternal–fetal interface is crucial for successful pregnancy and requires the interaction between the first trimester trophoblast and the endothelial cells of the maternal vessels. However, the precise mechanism of this dialog has yet to be determined. The current study investigated whether lysophosphatidic acid (LPA) modulates trophoblast–endothelial crosstalk in vitro. HTR‐8/SVneo trophoblast cell line (H8) was seeded on top of Geltrex, incubated with LPA or LPA + NS‐398 (selective cyclooxygenase‐2 inhibitor), LPA + 1400W (selective inducible nitric oxide synthase inhibitor) or LPA + IL‐6 neutralizing antibody and assayed for tube formation to model the acquisition of trophoblast endovascular phenotype. The supernatants were collected and used as conditioned media (CM). To test trophoblast–endothelial crosstalk, the endothelial cell line EA.hy926 was incubated with trophoblast CM. The CM from LPA‐induced tubulogenesis stimulated endothelial cells migration and did not modify the apoptosis. Soluble factors derived from cyclooxygenase‐2 and IL‐6 pathways were involved in H8–EA.hy926 interaction under the LPA effect. Moreover, LPA increased the levels of IL‐6 mRNA by cyclooxygenase‐2 pathway in H8 cells. Collectively, LPA promotes trophoblast–endothelial crosstalk in vitro and induces the release of trophoblast soluble factors that stimulate endothelial cells migration without changes in apoptosis. The evidence presented here provides new insights about an active role of LPA as a lipid mediator regulating vascular remodeling at the maternal–fetal interface. Abstract : The current study demonstrates that lysophosphatidic acid (LPA) promotes the interaction between the endovascular human first trimester trophoblast and endothelial cells at the maternal–fetal interface. This crosstalk depends on the secretion of LPA‐induced trophoblast soluble factors belonging to cyclooxygenase‐2 and IL‐6 pathways. Our findings shed new light on the significance of LPA signaling in the vascular events that lead to a successful pregnancy.